Hygienic Maintenance in Hypermarket / Nuraeaida Md Shah - Md Shah, Nuraeaida (2006)
In commerce, a hypermarket is a store which combines a supermarket and a department store and specialty stores under one roof. The result is a gigantic retail facility which carries an enormous range of products under one roof, including full lines of fresh groceries and apparel. When they are planned, constructed, and executed correctly, a consumer can ideally satisfy all of their routine weekly shopping needs in one trip to the hypermarket. Hypermarket can received more than 10 000 customer in a day. Every one seconds break will cause a million ringgit loss to the company. So, it needs a good planned maintenance system to overcome all the complaints or the damage without restrained the activity and the function of hypermarkets’ itself. It also must concerned of their names to make sure the customer will come back to buy products from them. Therefore they must fulfill and satisfy the customer needs. The availability of various selections of goods and the convenience offered by the hypermarket in reference to the clean, comfortable place, fresh and safe products makes customers enjoying to shopping and still coming every years. There are four famous hypermarket chains in Malaysia, such as Makro Hypermarket, Tesco Hypermarket, Giant Hypermarket and Carrefour Hypermarket.